Is preterm birth associated with asthma among children from birth to 17 years old? -A study based on 2011-2012 US National Survey of Children's Health - Jie Zhang; Chenchao Ma; Aimin Yang; Rongqiang Zhang; Jiannan Gong; Fengfeng Mo (BMC, 2018)
Abstract Background Preterm birth can interrupt lung development in utero and is associated with early life factors, which adversely affects the developing respiratory system. Studies on preterm birth and asthma risk are comparatively sparse and the results are not consistent. Methods Multivariate analyses were performed on a cross-sectional data from the National Survey of Children's Health (NSCH) collected in 2011 to 2012. The NSCH was a nationally representative telephone survey sponsored by the Maternal and Child Health Bureau and conducted by the National Center for Health Statistics. A cross-sectional analysis using data from the US on 90,721 children was conducted to examine the relationship between preterm birth and asthma risk. Results A total of 90,721 children under 17 years were included and 12% of the children were reported as preterm birth. The prevalence of diagnosed asthma was 15%, with a male to female ratio of 1.26:1. Children who were born preterm were 1.64 times (95% confidence interval: 1.45-1.84) more likely to develop asthma compared with those who were born term after controlling for confounders. Similarly, children who were low birth weight were 1.43 times (95% confidence interval: 1.25-1.63) more likely for asthma, and the odds ratio increased to 1.77 for those both preborn and low birth weight. Child's gender, race/ethnicity, age, family structure, family income levels, and household smoking were significantly associated with the odds of reported asthma. Conclusions Preterm birth was associated with increased risk of asthma among US children, supporting the notion that preterm birth may play a critical role in asthma development.